Air-Assisted Liquid–Liquid Microextraction (AALLME) as an Alternative Sample Pre-Treatment for Isolating Tetrahydrocannabinol (THC) from Hair - Laura Blanco-García; Pamela Cabarcos-Fernández; Iván Álvarez-Freire; María Jesús Tabernero-Duque; Antonio Moreda-Piñeiro; Ana María Bermejo-Barrera (Chemosensors, 2025)
Cannabis remains the most widely used illicit drug worldwide, identifying it is a routine procedure in forensic toxicology. Due to its widespread use, there is a need for analytical methods that can detect it in biological samples. Hair is of particular interest in forensic toxicology as it is the only biological sample that enables retrospective analysis of consumption. In addition, collecting hair is non-invasive, and the specimens can be stored at room temperature. However, the sample preparation process for hair is tedious and multi-step. To address this issue, this study introduces a novel approach to preparing hair samples for analysis, based on air-assisted liquid–liquid microextraction (AALLME). This technique is a modification of dispersive liquid–liquid microextraction (DLLME), which eliminates the need for dispersants and chlorinated organic solvents as extractants. Both techniques offer sustainable alternatives to conventional liquid–liquid extraction (LLE) and solid-phase extraction (SPE), making them of interest in forensic toxicology. This study is the first to report the application of AALLME to the hair matrix. A mixture of cyclohexane and ethyl acetate (9:1) was used as the extractant solvent. Gas chromatography–mass spectrometry (GC–MS) was then used to determine and quantify THC. The method was validated according to FDA guidelines and demonstrated good linearity within the 0.01–4 ng/mg range. The limits of detection (LOD) and quantification (LOQ) were 0.008 and 0.01 ng/mg, respectively. Finally, the applicability of the method was evaluated by analyzing hair samples received by the Forensic Toxicology Service.